IMF Survey, Volume 35, Issue 14. (IMF Survey; IMF Survey ;, 2006)
Seminar on preventing crises; Country briefs: Hong Kong SAR and Brazil; France's labor market reform; Seigniorage and governance; Chinese inflation; China's monetary policy; Mekong regional integration; Scaling up aid.